The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.20401/rasi.7.1.516
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Collaboration Networks in Bioenergy:

Abstract: This article analyzes the indicators of knowledge generation in sugarcane biomass. The impact of the FAPESP research program on bioenergy (BIOEN) is also analyzed, with a focus on the division of biomass and its subareas. Using detailed information from scientific articles in the subareas of Enzymatic hydrolysis, molecular markers, delignification, genotypes, enzymatic conversion, gene expression, nitrogen and photosynthesis, an evaluation of the international insertion of research and collaboration networks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…investigated all BIOEN‐related projects up to the year 2014, and concluded that there was little investment in logistics, and a greater concentration of related studies in the field and industry stages. In turn, the participation of the BIOEN program in the international biomass research network was investigated by Bueno et al ., 23 which identified the Brazilian predominance in the generation of scientific knowledge related to sugarcane biomass.…”
Section: Introductionmentioning
confidence: 99%
“…investigated all BIOEN‐related projects up to the year 2014, and concluded that there was little investment in logistics, and a greater concentration of related studies in the field and industry stages. In turn, the participation of the BIOEN program in the international biomass research network was investigated by Bueno et al ., 23 which identified the Brazilian predominance in the generation of scientific knowledge related to sugarcane biomass.…”
Section: Introductionmentioning
confidence: 99%